PERLINDUNGAN HUKUM TERHADAP ANAK HASIL NIKAH SIRRI YANG TIDAK TERCATAT PERSPEKTIF MAQASHID SYARIAH - Veny Novita Veronica; Marwin; Sukandi, Ahmad (LPPM Universitas Islam Ibrahimy Banyuwangi, 2026)
Unregistered marriage (nikah sirri) remains a social phenomenon in Indonesia that creates legal uncertainty regarding the status of children, particularly in relation to lineage, maintenance, inheritance, and custody rights. This study aims to analyze the legal protection afforded to children born from nikah sirri within the framework of maqāṣid al-syarī‘ah, with a specific focus on ḥifẓ al-nasl (protection of lineage). The research employs a normative juridical method with statutory, conceptual, and comparative approaches. Data were collected through library research by examining relevant primary, secondary, and tertiary legal materials. The data analysis was conducted using qualitative techniques, including legal interpretation (grammatical, systematic, and teleological) and comparative analysis. The validity of the data was ensured through source triangulation and consistency testing of legal arguments. The findings reveal that, from the perspective of Islamic law, nikah sirri that fulfills the essential pillars and conditions is considered valid. However, under Indonesian positive law, children born from such marriages are generally categorized as illegitimate (anak luar kawin) until a marriage validation (itsbat nikah) or judicial determination of lineage is issued. From the perspective of maqāṣid al-syarī‘ah, marriage registration or facilitation of itsbat nikah constitutes a ḍaruriyyat necessity to safeguard the welfare and comprehensive protection of children’s rights. Accordingly, this study recommends harmonization between Islamic law and positive law through the simplification of itsbat nikah procedures and the strengthening of child-centered policies that prioritize the best interests of the child.